2022
DOI: 10.1172/jci151725
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic microbes govern liver immunity by programming NKT cells

Abstract: The gut microbiome shapes local and systemic immunity. The liver is presumed to be a protected sterile site. As such, a hepatic microbiome has not been examined. Here, we showed a liver microbiome in mice and humans that is distinct from the gut and is enriched in Proteobacteria. It undergoes dynamic alterations with age and is influenced by the environment and host physiology. Fecal microbial transfer experiments revealed that the liver microbiome is populated from the gut in a highly selective manner. Hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 76 publications
1
35
0
Order By: Relevance
“…Furthermore, the bacterial structure and abundance of the GM was higher than that of the bile samples, but the bacterial diversity was lower than that of the bile bacterial community, indicating that some specific microbiota from the bile could colonize the GM and proliferate. In a recent study, the human duodenum and GB microbiome were closely clustered based on the Bray-Curtis dissimilarity matrix, suggesting that the GB microbiome has a close relationship with that of the small intestine ( 31 ). In teleost fish, the gut is roughly divided into three segments: the FG, MG, and HG ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the bacterial structure and abundance of the GM was higher than that of the bile samples, but the bacterial diversity was lower than that of the bile bacterial community, indicating that some specific microbiota from the bile could colonize the GM and proliferate. In a recent study, the human duodenum and GB microbiome were closely clustered based on the Bray-Curtis dissimilarity matrix, suggesting that the GB microbiome has a close relationship with that of the small intestine ( 31 ). In teleost fish, the gut is roughly divided into three segments: the FG, MG, and HG ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a very recent study demonstrated that the liver of both mice and humans harbors a microbiota, which is distinct from that of the gut. 10 This study suggested that the liver microbiota has dramatic impacts on liver immunity by modulating inflammatory cell recruitment and maturation through their microbiome-derived glycosphingolipids. The influence of this naive liver microbiota on liver regeneration is unknown.…”
Section: Main Textmentioning
confidence: 93%
“…However, most internal organs were long thought to be sterile. It is now broadly accepted that organs linked to the gut system harbor a low biomass of microbiota [ 16 , 25 ]. However, it is unknown whether microbial sites (upper or lower gastrointestinal tract) are associated with the pancreatic microbiome.…”
Section: The Microbiome In Healthy and Tumoral Pancreatic Tissuementioning
confidence: 99%